Synthesis of discrete catalytic oligomers and their potential in silica-supported cooperative catalysis. Issue 25 (7th May 2019) - Chandra, Prakash; Jonas, Alain M.; Fernandes, Antony E.
Abstract : The synthesis of discrete catalytic oligomers and their potential in supported cooperative catalysis are presented. Abstract : Cooperative catalysis on solid surfaces relies primarily on two or more catalytic partners being close enough to each other to sustain the catalytic cycle. We describe here the synthesis and preliminary investigation of discrete homo-oligomers as flexible scaffolds to inflect the intersite distance and blur the compositional heterogeneity in a silica-grafted catalytic triad.